2023
DOI: 10.1021/acssuschemeng.2c05064
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived Magnesium Oxide@Carbon Interlayer for Stable Lithium–Sulfur Batteries

Abstract: Lithium sulfur (Li–S) batteries represent a promising future battery technology. However, the low electrical conductivity of solid-state sulfur species (S, Li2S2, and Li2S) and the polysulfide shuttle effect deteriorate their practical capacity and cycling retention. Herein, we present an interlayer composed of magnesium oxide (MgO) nanoparticles and carbon matrix for the Li–S batteries. In the composite, MgO can capture dissolved polysulfides that diffuse to the carbon matrix along the oxide surface for furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…had reported that single metal oxide MnO 2 nanosheets as a functional interlayer exhibited capacity retention of only 93 % after 100 cycles at a low 0.2 C rate with an even lower sulfur loading of 0.7 mg cm −2 while Gope and Bhattacharyya [62] employed NiO as an interlayer which showed stable cycling stability only up to 100 cycles. Likewise, Kang et al [63] . reported on an MgO interlayer in carbon matrix which exhibited capacity retention of only 78.3 % after 200 cycles at 0.2 C rate.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…had reported that single metal oxide MnO 2 nanosheets as a functional interlayer exhibited capacity retention of only 93 % after 100 cycles at a low 0.2 C rate with an even lower sulfur loading of 0.7 mg cm −2 while Gope and Bhattacharyya [62] employed NiO as an interlayer which showed stable cycling stability only up to 100 cycles. Likewise, Kang et al [63] . reported on an MgO interlayer in carbon matrix which exhibited capacity retention of only 78.3 % after 200 cycles at 0.2 C rate.…”
Section: Resultsmentioning
confidence: 95%
“…Nazar et al [61] had reported that single metal oxide MnO 2 nanosheets as a functional interlayer exhibited capacity retention of only 93 % after 100 cycles at a low 0.2 C rate with an even lower sulfur loading of 0.7 mg cm À 2 while Gope and Bhattacharyya [62] employed NiO as an interlayer which showed stable cycling stability only up to 100 cycles. Likewise, Kang et al [63] reported on an MgO interlayer in carbon matrix which exhibited capacity retention of only 78.3 % after 200 cycles at 0.2 C rate. On the other hand, the TM-RE HEO interlayer in the present study exhibits long-term cycling stability at 0.5 C rate with as low a capacity decay of 0.08 % per cycle after 300 cycles at a comparatively higher sulfur loading of 1.5 mg cm À 2 .…”
Section: Resultsmentioning
confidence: 97%
“…The contribution of MOFs improves the active materials' utilization and the electrochemical performance by enhancing the trapping of polysulfides through chemisorption. [18][19][20] However, their poor electrical conductivity may limit their wide applications in Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ZIFs have been widely studied in the oxygen reduction/evolution reaction, hydrogen evolution reaction, lithium batteries, etc. 20,21 However, the specific surface area of ZIF-derived materials is generally small, and the performance of metal active sites is limited. 22,23 Herein, the cubic form of ZIF-67 is synthesized.…”
Section: ■ Introductionmentioning
confidence: 99%